Sanitasi Rumah Kos dan Perilaku Hidup Bersih Sehat (PHBS) Pada Penghuni Kos di Desa Tuntungan - Putri Alvia Aulina Ritonga; Nisrina Nisrina; Adinda; Adinda Aulia Aramdani; Dian Yustika Putri; Sufiah Adena Putri; Yusuf Syahputra Siregar; Ikhwanil Marwiah Sembiring (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Health development aims to increase awareness, ability, and willingness to live clean and healthy for everyone to realize decent housing in an orderly and healthy housing environment, in the sense that housing can be provided by its function in improving the quality of life. The purpose of this study is to improve knowledge, quality of health, and successful life behavior by implementing PHBS in rented houses in Tuntungan Village. The type of research used is observational research with descriptive analysis to better understand the cleanliness of boarding houses and clean and healthy living behavior (PHBS) conducted by boarding house fillers. Researchers took samples from 15 boarding house doors and 24 boarding house fillers who would fill out questionnaires. This study was conducted by comparing survey data with standards according to Minister of Health Regulation Number 1. 829/Menkes/SK/VII/1999 on housing health requirements. Results of interviews, observations, and measurements using questionnaires, checklists, and measuring instruments. The landlord conducts regular inspections of the building, by replacing parts that can no longer be used or can endanger the occupants, as well as repairing buildings that have long been damaged due to old age. It is necessary to make efforts to improve boarding facilities/rooms that are not yet qualified to improve the comfort of residents. Boarding house residents should follow the rules set by the boarding house owner and keep the boarding house or their belongings as appropriate. and implement clean and healthy living behaviors (PHBS).